Longitudinal Blood Pressure Control, Long-Term Mortality, and Predictive Utility of Serum Liver Enzymes and Bilirubin in Hypertensive Patients. Issue 1 (July 2015) - McCallum, Linsay; Panniyammakal, Jeemon; Hastie, Claire E.; Hewitt, Jonathan; Patel, Rajan; Jones, Gregory C.; Muir, Scott; Walters, Matthew; Sattar, Naveed; Dominiczak, Anna F.; Padmanabhan, Sandosh
<x xml:space="preserve">Abstract</x> There is accruing evidence from general population studies that serum bilirubin and liver enzymes affect blood pressure (BP) and cardiovascular risk, but it is unclear whether these have an impact on hypertensive patients in terms of long-term survival or BP control. We analyzed 12 000 treated hypertensive individuals attending a tertiary care clinic followed up for 35 years for association between baseline liver function tests and cause-specific mortality after adjustment for conventional cardiovascular covariates. Generalized estimating equations were used to study the association of liver tests and follow-up BP. The total time at risk was 173 806 person years with median survival 32.3 years. Follow-up systolic BP over 5 years changed by −0.4 (alanine transaminase and bilirubin), +2.1(alkaline phosphatase), +0.9(γ-glutamyl transpeptidase) mm Hg for each standard deviation increase. Serum total bilirubin and alanine transaminase showed a significant negative association with all-cause and cardiovascular mortality, whereas alkaline phosphatase and γ-glutamyl transpeptidase showed a positive association and aspartate transaminase showed a U-shapedassociation. Serum bilirubin showed an incremental improvement of continuous net reclassification improvement by 8% to 26% for 25 year and 35 year cardiovascular mortality, whereas all liver markers together improved continuous net reclassification improvement by 19% to 47% compared with reference model. In hypertensive patients, serum liver enzymes and bilirubin within 4 standard deviations of the mean show independent effects on mortality and BP control. Our findings would support further studies to elucidate the mechanisms by which liver enzymes and bilirubin may exert an effect on BP and cardiovascular risk, but there is little support for using them in risk stratification.